Retroperitoneal Lipoma Presenting with Nutcracker-Like Phenomenon - Seiichi Saito (Case Reports in Urology)
Retroperitoneal lipoma presenting with a nutcracker-like phenomenon is extremely rare. I experienced a case of a 65-year-old man presenting with left flank pain and macrohematuria intermittently for 3 years. Computed tomography revealed a lipoma at the left pedicle of the kidney, 30 mm in diameter, causing a curving of the left renal artery and dilatation of the left renal vein. This patient was treated successfully by retroperitoneoscopic resection of the lipoma. There have been no symptoms for 10 years after the operation.